The Influence of Digital Transformation on Teachers’ Job Performance in Nigerian Secondary Schools - Mubarak Lawal; Oba Ayoku; Ganiyat Mahmoud-kasandubu; Ridwan Fajenyo; Faruq Odumosu; Godwin Are (Journal of Education Technology, 2026)
The increasing integration of digital technologies in education presents both opportunities and challenges for enhancing teacher job performance. This study investigated the influence of digital transformation on teachers’ job performance, guided by four objectives, three research questions, and one hypothesis. The population comprised 6,939 secondary school teachers, with 360 teachers selected using a multistage sampling technique combining stratified and simple random sampling. Data were collected using a 30-item researcher-developed instrument, the Digital Transformation and Teachers’ Job Performance Questionnaire (DTTJPQ), validated by three experts and demonstrating high reliability (Cronbach’s alpha = 0.82). Findings reveal that digital transformation in secondary schools is ongoing but remains at a moderate level, constrained by infrastructural and technical limitations. The study further indicates a significant positive relationship between digital transformation and teacher job performance, suggesting that effective adoption of digital tools enhances instructional efficiency, engagement, and overall performance. Based on these findings, it is recommended that school authorities and policymakers provide adequate ICT facilities, including computers, projectors, and reliable internet connectivity, and support professional development programs to strengthen teachers’ digital competencies. The study contributes to the understanding of how digital transformation can be leveraged to improve educational outcomes and provides practical insights for educational planners and administrators seeking to optimize teacher effectiveness in digitally evolving learning environments.